Association of Circulating Neprilysin with BMI, Cardiovascular Health, and Kidney Function in High-Risk Pregnancies: A Pilot Study - Kaltrina Kutllovci Hasani; Azra Kulovic-Sissawo; Adam Saloň; Christina Stern; Karoline Mayer-Pickel; Mila Cervar-Zivkovic; Nandu Goswami; Herbert Fluhr; Ursula Hiden (Biomedicines)
Background/Objectives: Inadequate cardiovascular adaptation during pregnancy impairs endothelial function and vascular resistance, contributing to complications such as pre-eclampsia (PE) and gestational hypertension (GH). Neprilysin (NEP), a protease involved in vascular regulation, has been linked to PE, but its role in endothelial function and vascular adaptation remains unclear. This pilot study investigates the associations between soluble neprilysin (sNEP) and markers of vascular and renal function in high-risk pregnancies without PE. Methods: Observed parameters were analyzed in 29 high-risk pregnant women across early, mid-, and late pregnancy. sNEP levels were analyzed alongside body mass index (BMI), endothelial dysfunction (ADMA), arterial stiffness (pulse wave velocity, PWV), retinal microvasculature (central retinal arteriolar and venular equivalents, CRAE and CRVE), and kidney function markers. The impact of gestational hypertension (GH) and prior smoking on sNEP levels was also evaluated. Results: In early and mid-pregnancy, sNEP was inversely associated with BMI. During mid-pregnancy, sNEP showed a positive correlation with CRAE and an inverse correlation with PWV, suggesting reduced arterial stiffness. By late pregnancy, sNEP was positively associated with glomerular filtration rate and inversely correlated with creatinine and protein levels, reflecting improved kidney function. Women with GH exhibited elevated sNEP, while former smokers had lower sNEP levels in early pregnancy. Conclusions: These findings suggest that sNEP plays a role in vascular and renal adaption during pregnancy, offering new perspectives on vascular tone regulation in high-risk pregnancies. Further research is needed to clarify these mechanisms and their clinical relevance.